Italy : Staff Report for the 2012 Article IV Consultation. - International Monetary Fund. (Washington, D.C. : International Monetary Fund, 2012)
This 2012 Article IV Consultation focuses on Italy's economy, which is expected to continue contracting through the year owing to tight financial conditions, global slowdown, and the needed fiscal consolidation. The government has embarked on wide-ranging structural reforms to boost productivity and potential growth. Executive Directors have commended the Italian authorities for launching an ambitious policy agenda to secure fiscal sustainability and promote growth. Directors have also acknowledged the important steps taken toward deregulating the service sector and making the labor market more flexible and inclusive.
Off-Campus Access: No User ID or Password Required
On-Campus Access: No User ID or Password Required
Mode of access: Internet